The Role of Religion and Spirituality in Medical Patients in Germany - Büssing, Arndt (Journal of religion and health, 2005)
Using the new developed SpREUK questionnaire (version 1.0b), we examined how German patients (n = 129) with cancer, multiple sclerosis and other diseases view the impact of spirituality and religiosity (SpR) on their health and how they cope with illness. Patients with both a religious and spiritual attitude (32%) had significantly higher values in the sub-scales dealing with the search for meaningful support, and the stabilizing effects of SpR than patients without such attitudes (20%), while patients with a non-spiritual religious attitude (35%) had lower perception of the beneficial effects of their SpR and had significantly lower scores in the search for meaningful support sub-scale. Just half of the non-spiritual religious group and 42% of religious patients are convinced that finding an access to a spiritual source has a positive influence on their illness.